2007
DOI: 10.1111/j.1471-4159.2007.05136.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced behavioral sensitivity to the competitive GABA agonist, gaboxadol, in transgenic mice over‐expressing hippocampal extrasynaptic α6β GABAA receptors

Abstract: The behavioral and functional significance of the extrasynaptic inhibitory GABAA receptors in the brain is still poorly known. We used a transgenic mouse line expressing the GABAA receptor α6 subunit gene in the forebrain under the Thy‐1.2 promoter (Thy1α6) mice ectopically expressing α6 subunits especially in the hippocampus to study how extrasynaptically enriched αβ(γ2)‐type receptors alter animal behavior and receptor responses. In these mice extrasynaptic α6β receptors make up about 10% of the hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 46 publications
3
41
1
Order By: Relevance
“…It has been strongly suggested, based on data from native eGABARs, that the constrained GABA analogue THIP is a selective, nanomolar affinity ligand; however, recombinant studies of ␦ subunit-containing GABARs have led to the conclusion that there are uniform populations of receptors with much higher THIP EC 50 ranging from 3 to 53 M (Adkins et al 2001;Brown et al 2002;Jia et al 2005;Mortensen et al 2010;Saarelainen et al 2008;Storustovu and Ebert 2006). Here, we reconcile this discrepant THIP sensitivity between native eGABARs and recombinant forms of eGABARs.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It has been strongly suggested, based on data from native eGABARs, that the constrained GABA analogue THIP is a selective, nanomolar affinity ligand; however, recombinant studies of ␦ subunit-containing GABARs have led to the conclusion that there are uniform populations of receptors with much higher THIP EC 50 ranging from 3 to 53 M (Adkins et al 2001;Brown et al 2002;Jia et al 2005;Mortensen et al 2010;Saarelainen et al 2008;Storustovu and Ebert 2006). Here, we reconcile this discrepant THIP sensitivity between native eGABARs and recombinant forms of eGABARs.…”
Section: Discussionmentioning
confidence: 65%
“…Prior studies have used single-component Hill equations to derive EC 50 for THIP, and these estimates range from 6 to 53 M for ␣4␤2/3␦ receptors (Adkins et al 2001;Brown et al 2002;Jia et al 2005;Storustovu and Ebert 2006) and 3.1 to 8.2 M for ␣6␤3␦ receptors (Saarelainen et al 2008;Storustovu and Ebert 2006). This work suggested that the eGABAR dependence of the behavioral and cellular actions of THIP could not be accounted for by subunit-specific differences in sensitivity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…9B). Furthermore, 1 M THIP, a concentration that can selectively activate ␣6-and ␦-containing GABA A receptors (Storustovu and Ebert, 2006;Saarelainen et al, 2008), evoked 37.5 Ϯ 4.8 pA compared with 38.3 Ϯ 5.2 pA (n ϭ 11) of current for 1 M GABA within these dissociated granule neurons. These data suggest the presence of ␣6-and ␦-containing GABA A receptors within the dissociated granule neurons.…”
Section: Ketamine's Modulation Of Dissociated Granule Neuronsmentioning
confidence: 90%
“…However, THIP demonstrated an opposite effect, as it induced a long-lasting conditioned place aversion. We used an unbiased conditioning procedure to eliminate possible interference of anxiety and anxiolysis during the test (File, 1986;Parker et al, 1998), although THIP has poor anxiolytic efficacy in wild-type mice (Saarelainen et al, 2008). Although changes in the locomotor activity could have interfered with the expression of place preference (Gremel and Cunningham, 2007), this is unlikely because the locomotor activity during the tests was similar for the low-dose groups not showing aversion or preference and for the highest dose (6 mg/kg) group showing aversion.…”
Section: Lack Of Rewarding Effects Of Thip In Mice and Baboonsmentioning
confidence: 99%